Συζυγικά πορτρέτα στα νομίσματα και τα κοσμήματα της Ελληνιστικής περιόδου. (Νόμισμα / Κόσμημα. Χρήσεις - Διαδράσεις - Συμβολισμοί από την Αρχαιότητα έως Σήμερα., 2019)
Jugate portraits on coinage and jewellery of the Hellenistic period Jugate representations of divine or royal couples appear often on coins and seals in Graeco-Roman art. Putting an emphasis on dynastic integrity and continuity – derived from the model of their divine predecessors– the kings of the Hellenistic period (and particularly so the Ptolemies of Egypt) are shown next to their consorts as guarantors for the production of lawful heirs. As their divine model –devised, evidently, by themselves in anticipation of the symbolism they wished to put forward– they most commonly used Sarapis and Isis, a couple known to us from coins, seals and other such portable media, as well as a remote counterpart in the face of Zeus and Dione, a divine couple known from the coins and seals of Epirus. The emblematic value of coins or jewels employed as seals, such as engraved gemstones and signet rings, stresses the symbolism of the jugate scheme, rendering the image into an agent for Hellenistic kingship ideology. The type’s adoption by Roman Imperial couples strengthened its ideological content and guaranteed its survival well into modernity.